2014
DOI: 10.1016/j.virol.2014.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Initial characterization of Vaccinia Virus B4 suggests a role in virus spread

Abstract: Currently, little is known about the ankyrin/F-box protein B4. Here, we report that B4R-null viruses exhibited reduced plaque size in tissue culture, and decreased ability to spread, as assessed by multiple-step growth analysis. Electron microscopy indicated that B4R-null viruses still formed mature and extracellular virions; however, there was a slight decrease of virions released into the media following deletion of B4R. Deletion of B4R did not affect the ability of the virus to rearrange actin; however, VAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 133 publications
1
7
0
Order By: Relevance
“…1. Consistent with previous reports (Burles et al, 2014;Sumner et al, 2014), vP811 produced only very small foci on monolayers of BS-C-1 cells, but the plaques formed by vP759 were also significantly smaller than VACV Copenhagen (Fig. 2).…”
Section: Deletion Of 55 Orfs From the Genomic Termini Of Vacv Copenhasupporting
confidence: 92%
See 1 more Smart Citation
“…1. Consistent with previous reports (Burles et al, 2014;Sumner et al, 2014), vP811 produced only very small foci on monolayers of BS-C-1 cells, but the plaques formed by vP759 were also significantly smaller than VACV Copenhagen (Fig. 2).…”
Section: Deletion Of 55 Orfs From the Genomic Termini Of Vacv Copenhasupporting
confidence: 92%
“…Furthermore, in single-step growth curves, vP811 replicates as well as Copenhagen in BGMK and A549 cells, but forms smaller plaques than Copenhagen on BS-C-1, A549 and BGMK cells (Burles et al, 2014;Sumner et al, 2014). Poor replication in a multiple-step growth curve in BGMK cells, a small plaque phenotype and an observation of fewer actin tails all suggested that whilst viable in culture, vP811 has a defect in virus spread (Burles et al, 2014).…”
Section: Essential Genes As Defined By Conservation and Large Deletionsmentioning
confidence: 99%
“…#353180, BD Biosciences, Canada), in order to obtain perpendicular sections of cells on the membrane surface. Cells were then prepared for electron microscopic analysis as described before 48 with minor modifications: 2x conventional TEM fixative (mixture of glutaraldehyde (4%), paraformaldehyde (2%), sucrose (0.2 M) and CaCl 2 (4 mM), in 0.16 M sodium cacodylate buffer, pH 7.4) was added to the cell media to make optimally diluted fixative. Pre-fixation was performed at 37 °C for 1 hour.…”
Section: Methodsmentioning
confidence: 99%
“…Non-essential (Child et al, 1990, Gammon et al, 2010 HGT6 D1R Essential (Hassett et al, 1997) HGT7 A40R Non-essential (Wilcock et al, 1999) HGT8 A9L Essential (Yeh et al, 2000) HGT9 and HGT10 D9R Non-essential (Parrish and Moss, 2006) HGT11 B4R Non-essential (Burles et al, 2014) HGT12…”
Section: Hgt5 I4lmentioning
confidence: 99%